PERAN UNITED NATIONS EDUCATIONAL, SCIENTIFIC, AND CULTURAL ORGANIZATION (UNESCO) DALAM MENGATASI KERUSAKAN HUTAN HUJAN TROPIS SUMATERA (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
UNESCO is an international organization under the United Nations that focuses on the protection and preservation of world heritage sites. Indonesia as a member country of UNESCO has many world heritage sites recognized by UNESCO, one of which is the Tropical Rainforest Heritage of Sumatra. In 2011, this site received ‘in danger’ status from UNESCO due to the damage that occurred in the area caused by encroachment, illegal logging, road construction, invasive species, and the development of geothermal energy.The research is based on the role of international organizations theory, which contains the role of international organizations as facilitator, initiator, determinant, and mediator, as well as group level analysis to understand the role of a group about certain issues. This will demonstrate the role of UNESCO in dealing with certain issues. Data collection was carried out by using qualitative research methods, with data sourced from the official website of UNESCO, IUCN, the Indonesian government, books, journals, and news that discussed the destruction of the Tropical Rainforest Heritage of Sumatra. The results of this study shows that UNESCO plays a role in overcoming the destruction of the Tropical Rainforest Heritage of Sumatra. First as a initiator by providing recommendations through the World Heritage Committee session, IUCN Reactive Monitoring Mission, and Conservation Outlook, as well as in collaboration with Orangutan Center. Second, as facilitator by providing trust funds from World Heritage Fund and other parties to assist the conservation. Finally, as a determinator by reinstating Tropical Rainforest Heritage of Sumatra to be included in the World Heritage Danger List.Keywords: UNESCO, Indonesia, Tropical Rainforest Heritage of Sumatra, IUCN, Conservation